Improving Gender and Development Outcomes through Agency : Policy Lessons from Three Peruvian Experiences - Perova, Elizaveta (Lima: World Bank, 2013)
Peruvian public policy is currently focused on economic growth with social inclusion. The Ministry of Development and Social Inclusion (MIDIS)-created in October 2011-leads the sector and promotes evidence-based public policy using three strategic guidelines: 1) matching criteria and mechanisms for the selection of areas and target population, 2) generation of instruments for inter-sectorial and inter-governmental result-based coordination, and 3) activation of monitoring and evaluation procedures to measure interventions' progress and results. This study is about the incredible and frequently underestimated role of agency-the ability to make choices to achieve desired outcomes-in economic development. The authors share the view that agency has inherent value for development: it is an attribute and manifestation of development, or using Sen's words, it is constituent to development. This study however, focuses on the instrumental role of agency for more tangible manifestations of development, such as, poverty reduction and economic growth. It attempts to show that expanding individual agency is a powerful catalyst for improving welfare, as measured by these concrete and widely used metrics of policy success. Moreover, it argues that in many cases, improving development outcomes through agency is highly cost-effective. This study centers on several policy initiatives in Peru, which as will be subsequently shown, have improved the agency of their beneficiaries. The purpose of this study is twofold. First, it aims at bridging this information gap, providing a review of evidence that shows how the psychological components of agency, such as aspirations and self-esteem, can effectively contribute to more traditional development objectives-ranging from higher investments in human capital to increased income. Second, the study reviews and synthesizes research on several policy interventions in Peru, which have empowered their beneficiaries. In this way, the study aims to derive practical recommendations on how to incorporate psychological elements of agency into policy interventions in order to achieve better development outcomes. The study is structured as follows: the next section discusses the concept of agency, providing examples of its broad role in achieving development objectives. The following section reviews the quantitative and qualitative research that served as the basis for this study and elaborates on the methodologies used to derive the conclusions presented in the ensuing section. The last section synthesizes the conclusions of the review of different interventions in Peru into six practical 'policy lessons'.